Malaria in pregnancy as an indirect cause of infant mortality in sub-Saharan Africa. - Guyatt, H; Snow, R (2001)
Although randomized controlled trials of interventions to reduce malaria in pregnancy have demonstrated an increase in the birthweight of the newborn in primigravidae, the subsequent impact on infant mortality in all-parities has not been assessed. The aim of this paper was to model the possible impact of placental malarial infection on infant mortality through reduced birthweight. An extensive literature search was undertaken to define a series of parameters describing the associations between placental infection, birthweight and premature mortality in sub-Saharan Africa. It was shown that a baby is twice as likely to be born of low birthweight if the mother has an infected placenta at the time of delivery (all-parities: 23% vs 11%, primigravidae only: 32% vs 16%), and that the probability of premature mortality of African newborns in the first year of life is 3 times higher in babies of low birthweight than in those of normal birthweight (16% vs 4.6%). Assuming 25% of pregnant women in malaria-endemic areas of Africa harbour placental malarial infection, it is suggested that 5.7% of infant deaths in malarious areas could be an indirect cause of malaria in pregnancy. This would imply that, in 1997, malaria in pregnancy could have been responsible for around 3700 infant deaths under the diverse epidemiological conditions in Kenya. Placental infection with Plasmodium falciparum appears to have a more significant role in infant survival in Africa than has been previously assumed. This may explain the high reduction in infant mortality rates from interventions aimed at reducing transmission, over and above that expected from a decline in direct malaria-specific mortality alone.